1999
DOI: 10.1016/s0006-3495(99)77377-7
|View full text |Cite
|
Sign up to set email alerts
|

Sickle Hemoglobin Polymer Melting in High Concentration Phosphate Buffer

Abstract: Sickle cell hemoglobin (HbS) prepared in argon-saturated 1.8 M phosphate buffer was rapidly mixed with carbon monoxide (CO)-saturated buffer. The binding of CO to the sickle hemoglobin and the simultaneous melting of the hemoglobin polymers were monitored by transmission spectroscopy (optical absorption and turbidity). Changes in the absorption profile were interpreted as resulting from CO binding to deoxy-HbS while reduced scattering (turbidity) was attributed to melting (depolymerization) of the HbS polymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…HbS polymerization and gelation, which occur when HbS is in deoxy-state in the venous circulation, are considered the primary pathogenic event of sickle cell anemia (10)(11)(12)(13)(14)(15). Hence, the thermodynamics of HbS solutions (16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and the formation of the polymers and of other condensed phases (9,(26)(27)(28)(29)(30)(31) are studied as part of the fundamental mechanisms of the disease. These investigations have revealed that over periods of several days, HbS solutions form crystals (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…HbS polymerization and gelation, which occur when HbS is in deoxy-state in the venous circulation, are considered the primary pathogenic event of sickle cell anemia (10)(11)(12)(13)(14)(15). Hence, the thermodynamics of HbS solutions (16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and the formation of the polymers and of other condensed phases (9,(26)(27)(28)(29)(30)(31) are studied as part of the fundamental mechanisms of the disease. These investigations have revealed that over periods of several days, HbS solutions form crystals (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…It was suspected that the structural changes of HbS due to polymerization under hypoxic conditions might be reflected in the form of a variation in absorption [17]. Therefore, the absorption spectrum of the HbS protein was recorded and compared under hypoxia and normoxia conditions.…”
Section: Characterization Of Polymerization Of Hemoglobin S Under Hyp...mentioning
confidence: 99%
“…The assay is fast and economic screening technique that does not use whole sickle blood, rather commercially available purified sickle hemoglobin provided by Sigma-Aldrich. Hobs polymerization was achieved at a very low concentration of 50.0 µM by conducting the assay in high phosphate buffer (1.5M) medium [19]. Using as little as 250 µl of 40 mg/ml HBS solution; a given test compound can be evaluated at 5 different concentrations; each in quadruple, in a period of 20 minutes.…”
Section: Current Assaymentioning
confidence: 99%